The response of glass fibre reinforced PEKK laminates subjected to single and multiple impact loading - Nassier A. Nassir; R.S. Birch; W.J. Cantwell; Z.W. Guan (Polymer Testing, 2024)
This paper presents a study on the impact behaviour of newly-developed composites based on S-glass fibre reinforced PEKK (GF/PEKK) composites subjected to single and repeated impact loading. The laminates, with a thickness of 2 mm and fibre weigh fraction of 60 wt%, were manufactured by stacking eight plies of GF/PEKK woven prepregs using a hot compression moulding technique, and impacted centrally using a drop-weight apparatus. Beginning with a single impact test, these samples were subjected to repeated impacts using the same projectile and energy until full perforation was achieved. During each test, the impact response characteristics, contact force, velocity, displacement and energy absorption with respect to time were measured and recorded. The results show that, for a single impact test, the absorbed energy increases significantly at low impact energies, while repeated impacts lead to a decrease in the values of peak force and stiffness of the composite panels. Here, up to 5 times of energy can be absorbed over multiple low energy impacts compared to that required to perforate the target with a single impact. For multiple impacts at different impact energy levels, accumulation of damaged area increases rapidly around the impact location up to perforation failure (e.g. the rate of damage from 2 mm2 per impact at 1 J case jumping to 25 mm2 per impact at 2 J case, further to 68 mm2 per impact at 3 J case). The rate of damage progression (per impact) appears to be related strongly to the rate of energy absorption. The continuous nature of the absorbed energy and damage progression over multiple impacts suggest that semi-empirical analytical relationships, similar to that used in a fatigue analysis, could be useful in providing a means of assessing impact damage in a laminated structure and predicting the remaining ‘impact fatigue’ life.